VD_FINDINFO HC / 2021 / 286 vom 19. April 2021 - VD Tribunal cantonal (2021)
DÉCISION ÉTRANGÈRE, RECONNAISSANCE DE LA DÉCISION, DÉBITEUR | 291 CC, 33 al. 1 CL, 34 CL, 43 al. 1 CL, 43 al. 2 CL, 335 al. 3 CPC (CH)